Monoclonal Antibodies for Protozoan Infections: A Future Reality or a Utopic Idea? - Longoni, Silvia Stefania; Tiberti, Natalia; Bisoffi, Zeno; Piubelli, Chiara (Frontiers in Medicine, 2021)
Following the SARS-CoV-2 pandemic, several clinical trials have been approved for the investigation of the possible use of mAbs, supporting the potential of this technology as a therapeutic approach for infectious diseases. The first monoclonal antibody (mAb), Muromonab CD3, was introduced for the prevention of kidney transplant rejection more than 30 years ago; since then more than 100 mAbs have been approved for therapeutic purposes. Nonetheless, only four mAbs are currently employed for infectious diseases: Palivizumab, for the prevention of respiratory syncytial virus (RSV) infections, Raxibacumab and Obiltoxaximab, for the prophylaxis and treatment against anthrax toxin and Bezlotoxumab, for the prevention of Clostridium difficile recurrence. Protozoan infections are often neglected diseases for which effective and safe chemotherapies are generally missing. In this context, drug resistance and drug toxicity are two crucial problems. The recent advances in bioinformatics, parasite genomics, and biochemistry methodologies are contributing to better understand parasite biology, which is essential to guide the development of new therapies. In this review, we present the efforts that are being made in the evaluation of mAbs for the prevention or treatment of leishmaniasis, Chagas disease, malaria, and toxoplasmosis. Particular emphasis will be placed on the potential strengths and weaknesses of biological treatments in the control of these protozoan diseases that are still affecting hundreds of thousands of people worldwide.